PENGARUH RASIO PROFITABILITAS TERHADAP PERUBAHAN HARGA SAHAM PADA PERUSAHAAN SEKTOR PROPERTI YANG LISTING DI BURSA EFEK INDONESIA PERIODE 2008-2012 - FERI, MOCHAMAT (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract: Stock is one type of investment is quite attractive and the most heavily traded in the capital market. In principle, investors buy stocks is to earn dividend and sell the stock at a higher price (capital gain).The purpose of this research is to determine the influence of OPM, ROE, NPM and ROA toward changes in stock prices on property sector companies that listed in Indonesia Stock Exchange period 2008-2012 simultaneously and partially. Sample in this research a total of 27 companies were taken using purposive sampling method. Data collection method use is documentation. Data analysis method used is multiple linier regression. The results of this research show that simultaneously there is significant influence between the independent variable to the dependent variable. While partially only ROE variables has a significant influence to changes stock prices. OPM, NPM, ROA variables had no effect on stock prices changes. Keywords: OPM, ROE, NPM, ROA, and stock price changes.